THE PHYSICOCHEMICAL AND SENSORY QUALITY OF BAUNG (Hemibagrusnemurus) IS FED A MIXED DIET OF SALTED TRASH FISH AND FISH INNARDS AS A SUBSTITUTE FOR CONVENTIONAL FISH MEAL - Hutagaol, Debby Alvionita; Hasan, Bustari; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was purpose to evaluate physicochemical and sensory characteristics of baung catfish fed diet containing the mixture of salted trash fish and catfish viscera replacement in fish diet. Baung catfish avaranging ±50 gram in weight were diet containing the mixture of salted trash fish and catfish viscera replacing for covensional fishmeal 0% (TIK), 50% (CIRJ 50), 75% (CIRJ 75), 100% (CIRJ 100) and commercial. The fish were fed in floating net up to commercial size (±500g). The harvested fish were evaluated for physicochemical (edible portion, processing waste, proximate composition, non protein nitrogen and amino acid) and sensory characteristics. The result indicated there were no significant difference in physicochemical characteristics and sensory quality. The fish fed the difference diets, those, it can be concluded that a mixture of salted trash fish and fish visceral can replace convensional fishmeal in the fish diet. Keywords:Baung, Physicalchemistry, Sensory, Trash Fish, Fish Innards